Community Deprivation Index and Discharge Destination After Elective Hip Replacement. Issue 4 (26th March 2021) - Mehta, Bella; Goodman, Susan; Ho, Kaylee; Parks, Michael; Ibrahim, Said A.
Abstract : Objective: To examine how the deprivation level of the community in which one lives influences discharge disposition and the odds of 90‐day readmission after elective total hip arthroplasty (THA). Methods: We performed a retrospective cohort study on 84, 931 patients who underwent elective THA in the Pennsylvania Health Care Cost Containment Council database from 2012 to 2016. We used adjusted binary logistic regression models to test the association between community Area Deprivation Index (ADI) level and patient discharge destination as well as 90‐day readmission. We included an interaction term for community ADI level and patient race in our models to assess the simultaneous effect of both on the outcomes. Results: After adjusting for patient‐ and facility‐level characteristics, we found that patients from high ADI level communities (most disadvantaged), compared to patients from low ADI level communities (least disadvantaged), were more likely to be discharged to an institution as opposed to home for postoperative care and rehabilitation (age <65 years adjusted odds ratio [ORadj ] 1.47; age ≥65 years ORadj 1.31; both P < 0.001). The interaction effect of patient race and ADI level on discharge destination was statistically significant in those patients age ≥65 years, but not in patients age <65 years. The association with ADI level on 90‐day readmission was not statistically significant. Conclusion: In this statewide sample of patients who underwent elective THA, the level of deprivation of the community in which patients reside influences their discharge disposition, but not their odds of 90‐day readmission to an acute‐care facility.